Easter Week Visit to Albert Watkins and Rose Watkins in Huntington Beach - Watkins, Howard::::::::: (1984)
Rose Watkins holding Robin Watkins, Adam Watkins, Albert Watkins; white fence with mailboxes and 207 showing